PREFERENSI PEMANGKU KEPENTINGAN DALAM PENGELOLAAN HUTAN PRODUKSI: STUDI KASUS DI KESATUAN PEMANGKUAN HUTAN BOGOR - Triyono Puspitojati; Dudung Darusman; Rudy C. Tarumingkeng; Boen Purnama (Jurnal Analisis Kebijakan Kehutanan, 2012)
Forest management systems formulated by forest concesion firm in Java was not suitable to manage production forest sustainably. This study tried to formulate production forest management system based on 9 (nine) groups of stakeholders' preferences. The objectives of this study were (1) to find out preferences of stakeholders on production forest management and (2) to formulate the production forest management system matching with stakeholders' preferences. The results of this study were as follows. , the stakeholders' preferences were: (1) rural people participate on production forest management activities. This can be brought into reality by placing empowerment as part of production forest management activities; (2)Rural people had a job continously on production forest management. This can be brought into reality by managing production forest multiculturally which products can be harvested yearly; and (3) Rural people participate on activities related to production forest management. This can be brought into reality by subjected them as the partner of forest concesion firm on private forest management, forestry production inputs and forest products industries. Second the production forest management system matching with stakeholders' preferences was multiculture production forest management system based on rural people empowerment which subjected rural people as the partner of forest concession firm on forest management, forest products industries and forestry production inputs.